Wild Boars as an Indicator of Environmental Spread of ESβL-Producing Escherichia coli - Mercato, Alessandra; Cortimiglia, Claudia; Abualsha’ar, Aseel; Piazza, Aurora; Marchesini, Federica; Milani, Giovanni; Bonardi, Silvia; Cocconcelli, Pier Sandro; Migliavacca, Roberta (Frontiers in Microbiology, 2022)
The Antimicrobial Resistance (AMR) represents an increasing issue worldwide, spread not only in humans and farmed animals, but also in the wildlife. One of the most relevant problems is represented by Extended Spectrum Beta-Lactamases (ESβLs) producing Escherichia coli, because they are cause of important infections in humans. Wild boars (Sus scrofa) as a source of ESβLs attracted attention because of the increasing density and their habits that lead them to be at the human-livestock-wildlife interface. The aim of this study is to increase the knowledge about the ESβLs E. coli strains carried by wild boars living in a particularly high-density area of Northern Italy. The analysis of 60 animals allowed to isolate 16 ESβLs-producing E. coli strains (prevalence 23.3%), which were characterized from a phenotypical and molecular point of view. The overall analysis revealed that the 16 isolates were all not only ESβLs producers, but also multi-drug resistant and carried different types of plasmid replicons. The genome analysis performed on a subset of isolates confirmed the heterogeneity observed with PFGE and highlighted the presence of two pandemic sequence types, ST131 and ST10, with different collection of virulence factors. The genomic context of ESβLs genes further evidenced that all of them were surrounded by transposons and insertion sequences, suggesting the possibility to exchange AMR genes. Overall, this study showed the worrying dissemination of ESβLs-producing E. coli in wild boars in Northern Italy, suggesting the role of these animals as spreader of AM resistance and their inclusion in surveillance programs, to shed light to the “One Health” complex interactions.